Examining the multidimensional impact on soft drink packaging preferences through the unified model of aesthetics - Ding, Sinong; Yahaya, Mohd Faiz; Abdul Rahman, Ahmad Rizal (Nature Research, 2025)
Consumer psychology has been proven to have an essential influence on aesthetic preferences. Previous research on aesthetics focused on long-lasting product categories and was conducted at a single level. However, aesthetics is multidimensional, which has been overlooked. Our research is based on the unified model of aesthetics (UMA), which aims to investigate the unique contributions of the perceptual (unity, variety), cognitive (typicality, novelty), and social (connectedness, autonomy) levels to aesthetic preferences for packaging designs. The studies used soft drink packaging from the fast-moving consumer goods (FMCG) category as stimuli, and Chinese participants evaluated the packaging on a 7-point Likert scale. Study 1 shows that people gravitate toward safety over accomplishment and that connectedness, typicality, and unity are the main determinants of aesthetic pleasure. Study 2 added two scenarios: for “going to a very formal meeting,” stimuli with unity, typicality, and connectedness could best induce aesthetic pleasure. For “going to a good friend’s rave party,” the novelty, autonomy, and variety of designs were the most pleasing. Furthermore, two studies showed that for the overall stimulus, unity consistently evoked more positive aesthetic preferences than variety. Overall, this research provides new insights into aesthetic influences at the perceptual, cognitive, and social levels in soft drink packaging and offers new perspectives on aesthetic preferences for new product development.